Consultoria colaborativa como estratégia para promover inclusão escolar em aulas de educação física - Oliveira, Patricia Santos de (2018)
Collaborative consulting is a support service model that aims to help teachers with the inclusive education process of students with disabilities. This service model has emerged in the Brazilian literature related to Special Education as a possibility of a service in the Specialized Educational Service. However, although advances are taking place, few studies have investigated this support model intended for the area of Physical Education. Thus, it is important to investigate how the collaborative consulting support service can help face the challenges encountered by Physical Education teachers at schools who work in inclusive contexts in Brazil. Considering the above, the overall objective of the study is to plan, implement and evaluate a collaborative consulting program as a model for inclusion support in the context of Physical Education in schools. To do so, collaborative field research was conducted in which a consulting program was developed. Three teachers from regular schools who taught classes to students with disabilities participated in this study. The program was developed in four stages: 1) Building up and establishing relationships with the school community; 2) Identifying and defining the problem to be solved and planning the action plan; 3) Implementing the collaborative consulting program; and 4) Evaluating the Collaborative Consulting program. In order to plan the program, after building up a relationship with the school and the teachers, a survey was conducted of the difficulties encountered by each teacher. Then, based on the demands that emerged, the program was planned, carried out and later evaluated from the teachers’ perspective. Thus, three intervention programs were developed in parallel, which aimed to provide support services to physical education teachers based on collaboration. For each of the three programs, the following was defined as the demand for problem solving, respectively: a change in attitudes towards students with disabilities; student behavior management and the participation of students with disabilities in Physical Education classes. The results indicate that the collaborative consulting service in Adapted Physical Education was shown as a viable possibility of a strategy to support inclusion in the context of Physical Education classes, which can help general physical education teachers feel more confident when dealing with the challenges of school inclusion. From the point of view of the participating teachers, the program had an effect mainly on overcoming the limitations imposed by the lack of diagnosis and recognition and appreciation of the pedagogical practice of the teacher. However, for such actions to be possible, public policies need to be created that sustain support strategies based on collaboration in the municipal and state education networks, to make collaborative consulting a permanent service to support physical education teachers.